2021
DOI: 10.1039/d1tb00071c
|View full text |Cite
|
Sign up to set email alerts
|

2D materials as a diagnostic platform for the detection and sensing of the SARS-CoV-2 virus: a bird's-eye view

Abstract: Worldwide infection and fatality by SARS-CoV-19 virus and its variants responsible for COVID 19 have impeded economic growth of developing nations beyond repair, General public in several nations have lost...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 119 publications
0
12
0
Order By: Relevance
“…In addition, this group confirmed the antiviral function of these natural composites that can be used in order to enhance the barrier effect of surgical masks [130]. They demonstrated that human viruses such as human adenovirus HAdV5 or human coronavirus HCoV229E were sensitive to compounds with a valuable content of polyphenols, such as hydroalcoholic extracts of clove blossoms, olive leaves, or green tea [130] (see excellent antiviral properties [49,50]. However, further studies are warranted for the functionalization of these materials on communal objects (e.g., mask, door handles, elevator buttons, gas pumps, and railings) to reduce both disease transmission and fear of touching objects.…”
Section: Natural Compoundsmentioning
confidence: 78%
See 3 more Smart Citations
“…In addition, this group confirmed the antiviral function of these natural composites that can be used in order to enhance the barrier effect of surgical masks [130]. They demonstrated that human viruses such as human adenovirus HAdV5 or human coronavirus HCoV229E were sensitive to compounds with a valuable content of polyphenols, such as hydroalcoholic extracts of clove blossoms, olive leaves, or green tea [130] (see excellent antiviral properties [49,50]. However, further studies are warranted for the functionalization of these materials on communal objects (e.g., mask, door handles, elevator buttons, gas pumps, and railings) to reduce both disease transmission and fear of touching objects.…”
Section: Natural Compoundsmentioning
confidence: 78%
“…The threat of the SARS-CoV-2 virus has prompted researchers to combine their work in interdisciplinary areas. In this regard, materials science and nanotechnology have significantly contributed to the fight against virus outbreaks, by successfully synthesizing different types of materials with excellent antiviral properties. , However, further studies are warranted for the functionalization of these materials on communal objects (e.g., masks, door handles, elevator buttons, gas pumps, and railings) or other protective equipment such as face shields, goggles, helmets, plastic masks, and space separation screens like those used for counters or vehicles to reduce both disease transmission and anxiety with regard to touching objects. The face mask industry is progressing very rapidly by incorporating a broad range of technological advances.…”
Section: Future Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relevance of biosensors that are both highly sensitive and specific, with easy translation into portable health applications, has been particularly highlighted by the need for rapid screening of large populations during the SARS-CoV-2 pandemic 1 . Surface-Enhanced Raman Scattering (SERS)-based immunosensors are especially suited to fulfil the criteria of highly sensitive and specific analyte detection, with easy adaptation to a variety of point-of-care testing (POCT) formats.…”
Section: Introductionmentioning
confidence: 99%